HUBUNGAN SELF-EFFICACY DAN SIKAP POSITIF TERHADAP PRESTASI AKADEMIK SISWA SMK NEGERI 1 SIPIROK - Yulia Anita Siregar; Sukatno Sukatno (MES: Journal of Mathematics Education and Science, 2017)
Self-efficacy is a person's feelings, ways of thinking, self-motivation, and desire to have something, while a positive attitude means in the learning process students have a tendency to accept or reject a concept or idea, if not in accordance with his mind. Students can think and be positive if if a learning can provide real benefits for life. While the academic achievement is the result of behavioral changes that include the cognitive domain, affective domain and psychomotor domain which is a measure of student success after being given treatment or learning. This research was conducted at SMK Negeri 1 Sipirok. This study uses descriptive research method with correlational approach with the aim to know whether there is a significant relationship between self-efficacy and positive attitude toward student academic achievement. Based on the research that has been done, the research results found that there is a significant relationship between self-efficacy and positive attitude of students to the academic achievement in SMK Negeri 1 Sipirok Tapanuli Selatan but the relationship is not showing increase or decrease so it can be said academic achievement is not important enough in pushing self-efficacy and positive attitude of students.